Small RNA-sequencing reveals the involvement of microRNA-132 in benzo[a]pyrene-induced toxicity in primary human blood cells. (1st July 2023) - Souki, Rima; Amosse, Jérémy; Genêt, Valentine; Le Gall, Morgane; Saintpierre, Benjamin; Letourneur, Franck; Maître, Anne; Demeilliers, Christine; Le Ferrec, Eric; Lagadic-Gossmann, Dominique; Podechard, Normand; Sparfel, Lydie
Abstract: Polycyclic aromatic hydrocarbons (PAHs) are widely distributed environmental contaminants, triggering deleterious effects such as carcinogenicity and immunosuppression, and peripheral blood mononuclear cells (PBMCs) are among the main cell types targeted by these pollutants. In the present study, we sought to identify the expression profiles and function of miRNAs, gene regulators involved in major cellular processes recently linked to environmental pollutants, in PBMC-exposed to the prototypical PAH, benzo[ a ]pyrene (B[ a ]P). Using small RNA deep sequencing, we identified several B[ a ]P-responsive miRNAs. Bioinformatics analyses showed that their predicted targets could modulate biological processes relevant to cell death and survival. Further studies of the most highly induced miRNA, miR-132, showed that its up-regulation by B[ a ]P was time- and dose-dependent and required aryl hydrocarbon receptor (AhR) activation. By evaluating the role of miR-132 in B[ a ]P-induced cell death, we propose a mechanism linking B[ a ]P-induced miR-132 expression and cytochromes P-450 (CYPs) 1A1 and 1B1 mRNA levels, which could contribute to the apoptotic response of PBMCs. Altogether, this study increases our understanding of the roles of miRNAs induced by B[ a ]P and provides the basis for further investigations into the mechanisms of gene expression regulation by PAHs. Graphical abstract: Image 1 Highlights: Small RNA sequencing identifies B[ a ]P-responsive miRNAs in human PBMCs. Predicted targets of B[ a ]P-regulated miRNAs are related to apoptosis of PBMCs. miR-132–3p is the most B[ a ]P-regulated miRNA in PBMCs. B[ a ]P-induced miR-132 requires AhR activation. miR-132 could modulate apoptosis via regulation of the CYP1A1/1B1 balance upon B[ a ]P.